The efficacy of hypothermia combined with thrombolysis or mechanical thrombectomy on acute ischemic stroke: a systematic review and meta-analysis - Wang, Dan; Yan, Dan; Yan, Mingmin; Tian, Hao; Jiang, Haiwei; Zhu, Bifeng; Chen, Yu; Peng, Tao; Wan, Yue (Frontiers in Neurology, 2025)
BackgroundTherapeutic hypothermia improves outcomes in experimental stroke models, especially after ischemia-reperfusion injury. In recent years, the safety and efficacy of hypothermia combining thrombolysis or mechanical thrombectomy have attracted widespread attention. The primary objective of the study was to evaluate the effectiveness and safety of hypothermia by combining reperfusion therapy in acute ischemic stroke patients.MethodsA systematic search was performed in PubMed, EMBASE, Cochrane Library, and the Clinical Trial Registries on articles published until May 2024. The full-text articles were thoroughly reviewed, and relevant information regarding study characteristics and outcomes was extracted. Mantel–Haenszel (M–H) random-effects model was used to calculate pooled risk ratios (RR) with 95% confidence intervals (CI). In addition, subgroup analyses were performed focusing on the different hypothermia modalities and duration.ResultsAfter screening 2,265 articles, 10 studies were included in the present analysis with a total sample size of 785. Forest plots of clinical outcomes were as follows: modified Rankin Scale (mRS) ≤2 at 3 months (RR = 1.28, 95% CI 1.01–1.61, p = 0.04), mortality within 3 months (RR = 0.95, 95% CI 0.69–1.29, p = 0.73), total complications (RR = 1.02, 95% CI 0.89–1.16, p = 0.77) and pneumonia (RR = 1.35, 95% CI 0.76–2.40, p = 0.31). Subgroup analyses indicated a mild protective effect of selective cerebral hypothermia; however, the difference in mortality between the hypothermia and control groups was not statistically significant (RR = 0.88, 95% CI 0.57–1.35, p = 0.55). Patients undergoing hypothermia for 24–48 h experienced a higher rate of overall complications (RR = 1.37, 95% CI 1.01–1.86, p = 0.04) and pneumonia (RR = 2.84, 95% CI 1.05–7.66, p = 0.04).ConclusionThe preliminary evidence supports the safety and feasibility of hypothermia combined with reperfusion therapy, which should be further investigated in randomized controlled studies.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024556625.